1985
DOI: 10.1038/bjc.1985.146
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength and light-dose dependence in tumour phototheraphy with haematoporphyrin derivative

Abstract: Summary Red light (c. 630 nm) is almost universally used in tumour phototherapy as it is the most penetrating of the porphyrin excitation wavebands. However, measurements of tumour attenuation of light of different wavelengths and of the excitation spectrum of haematoporphyrin derivative in vitro suggested that green light might be more efficient than red in destroying thin tumours. Experimentally, we confirmed this for tumours up to -1.2mm thick, a depth exceeding that of most carcinomas-in-situ. The superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Undesirable deep tissue damage can therefore be avoided, while keeping a high degree of PDT efficacy at lesser depths. Experimental animal studies have confirmed that HPD photosensitization with green light at 514 nm is very effective in inducing superficial tissue necrosis to depths of up to 2-3 mm (Bellnier et al, 1985;van Gemert et al, 1985). Our endoscopic examination 7-10 days after PDT showed superficial tissue necrosis in all instances without any real macroscopic difference in the amount of damage between the two treatment wavelengths.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Undesirable deep tissue damage can therefore be avoided, while keeping a high degree of PDT efficacy at lesser depths. Experimental animal studies have confirmed that HPD photosensitization with green light at 514 nm is very effective in inducing superficial tissue necrosis to depths of up to 2-3 mm (Bellnier et al, 1985;van Gemert et al, 1985). Our endoscopic examination 7-10 days after PDT showed superficial tissue necrosis in all instances without any real macroscopic difference in the amount of damage between the two treatment wavelengths.…”
Section: Discussionsupporting
confidence: 64%
“…Only a few preclinical (Bellnier et al, 1985;van Gemert et al, 1985;Nseyo et al, 1993;Foster et al, 1996;Nauta et al, 1996) and clinical (Bandieramonte et al, 1984;Delaney et al, 1993) PDT studies have been reported with the 514.nm laser light after photosensitization with Photofrin II or HPD. These studies have demonstrated that the destruction of a thin layer of superficial neoplastic tissue is possible, and that tumour necrosis of up to 2-3 mm could be obtained.…”
mentioning
confidence: 99%
“…Selective PDT-induced vascular damage in tumours, with less impressive damage in normal tissue vessels, has been demonstrated in several studies (Tromberg et al, 1990;Reed et al, 1989). It is also clear that there is a threshold (of both light and drug dose) for PDT effect (Bown et al, 1986;Van Gemert et al, 1985), and this threshold may be higher for normal tissue than for tumour. Photobleaching, which is known to be substantial for mTHPC (Ma et al, 1994), may play an important role in keeping drug levels below the threshold value and helping to selectively spare the normal tissue.…”
Section: Discussionmentioning
confidence: 91%
“…The depth of penetration of 630 nm light (used for Photofrin and ALA) in tissue ranges from 0.2 to 2 cm. 55,[73][74][75][76] The mean depth of destruction of rectal and sigmoid adenocarcinomas in patients receiving Photofrin amounts to 0.6 cm, with a range of 0.3 to 1.5 cm, after intraluminal insertion of an optical fiber 1 mm into the tumor. 77 Among factors that limit light penetration are the presence of blood clot and necrosis within the tumor and absorption of light by the photosensitizer itself (a phenomenon called self-shielding).…”
Section: Limitationsmentioning
confidence: 99%